2024
DOI: 10.1021/acs.langmuir.3c03698
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Alumina Membrane Filters with Framework Structures by Al Anodization

Youta Boushi,
Takashi Yanagishita

Abstract: Alumina membrane filters consisting of a thin filter layer (200−700 nm in thickness) supported by a framework (30−100 μm in thickness) were fabricated on the basis of the anodization of an Al substrate. The solution permeability of alumina membrane filters with tubular pores of uniform size and shape varies with membrane thickness; therefore, membrane filters with a filter layer thickness of less than 1 μm showed high solution permeability. Although the filter layer is thin, it is reinforced by a thick framewo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 54 publications
0
0
0
Order By: Relevance
“…We believe that further improvement of the pore size uniformity by improving the conditions of anodization and ALD will enable the reduction in error. In our previous study, alumina membranes with frameworks were found to have a higher permeability than commercial membrane filters with similar pore sizes . The permeation properties of the alumina membranes obtained by this process depend on the structure of the framework and the thickness of the thin filter layer; thus, further improvement of permeation properties is expected to be possible even when the pore size is reduced to a single nanometer by optimizing these structures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We believe that further improvement of the pore size uniformity by improving the conditions of anodization and ALD will enable the reduction in error. In our previous study, alumina membranes with frameworks were found to have a higher permeability than commercial membrane filters with similar pore sizes . The permeation properties of the alumina membranes obtained by this process depend on the structure of the framework and the thickness of the thin filter layer; thus, further improvement of permeation properties is expected to be possible even when the pore size is reduced to a single nanometer by optimizing these structures.…”
Section: Resultsmentioning
confidence: 99%
“…It is necessary to resolve this incompatibility to expand the range of applications of alumina membranes. In our recent study, we developed a novel fabrication method for highly permeable and durable alumina membranes . Alumina membranes consisting of a thick framework layer that functions as a support film and a thin filter layer that functions as a filtration film were fabricated by the combination of the anodization and selective etching of the anodic oxide layer using a resist mask.…”
Section: Introductionmentioning
confidence: 99%